2018
DOI: 10.1007/s10439-018-2020-z
|View full text |Cite|
|
Sign up to set email alerts
|

A Semi-passive Planar Manipulandum for Upper-Extremity Rehabilitation

Abstract: Robotic rehabilitation is a promising approach to treat individuals with neurological or orthopedic disorders. However, despite significant advancements in the field of rehabilitation robotics, this technology has found limited traction in clinical practice. A key reason for this issue is that most robots are expensive, bulky, and not scalable for in-home rehabilitation. Here, we introduce a semi-passive rehabilitation robot (SepaRRo) that uses controllable passive actuators (i.e., brakes) to provide controlla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Depending on the dimension n of the device taskspace and the dimension of C q,k ⊥ , motion with a certain valve setting may be allowed in all directions (p = n, as when all cylinders are connected to the reservoir), a single heading (p = 1), or a higher dimensional manifold 7 (e.g., when C q,k ⊥ ∈ 3×2 , a p = 2 plane through a 3D space is imposed).…”
Section: B Application To Digital Hydraulicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the dimension n of the device taskspace and the dimension of C q,k ⊥ , motion with a certain valve setting may be allowed in all directions (p = n, as when all cylinders are connected to the reservoir), a single heading (p = 1), or a higher dimensional manifold 7 (e.g., when C q,k ⊥ ∈ 3×2 , a p = 2 plane through a 3D space is imposed).…”
Section: B Application To Digital Hydraulicsmentioning
confidence: 99%
“…To the operator, ideal motion guidance feels like a hard wall, curve, or surface. Motion-guiding robots have been developed to facilitate human/robot collaborative assembly operations [1], to perform haptic rendering [2], to train manual skill [3], [4], and to rehabilitate motor function after neurological injury [5], [6], [7]. Both in manual skill training and robotic rehabilitation, it has been suggested that the human should take an active role to maximize therapeutic or training effects [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al proposed a modular and reconfigurable wrist robot called CR2-Haptic for post-stroke subjects to train forearm and wrist movements [ 7 ]. Besides, many other end-effector-based therapeutic robot have been investigated and can be referred to [ 8 , 9 , 10 , 11 , 12 , 13 ]. Comparatively, the exoskeleton-based rehabilitation robots are developed with more complex structures imitating the anatomical human skeleton and guaranteeing the alignment between the joints axis of robot and impaired limb.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al developed a semi-passive rehabilitation robot for patients with neurologic or orthopedic disorders. 3 The device was validated through theoretical analyses, hardware experiments, and human subject testing, and showed potential for use as a low-cost therapeutic tool for upper-extremity rehabilitation.…”
mentioning
confidence: 99%